Conflicting Experiences With Welcoming Encounters: Narratives of Newly Arrived Refugees in the Netherlands - Younes Younes; Halleh Ghorashi; Elena Ponzoni (Social Inclusion, 2021)
Personal networks can be both enabling and constraining in inclusion practices. This study focuses on the contribution of a particular neighborhood initiative for refugees in Amsterdam. Earlier studies have shown that in the specific context of the Netherlands’ welfare state, institutional or citizen initiatives can constrain the actual inclusion of refugees. These studies argue that good intentions do not necessarily lead to inclusion because hierarchal relations reproduce subtle exclusionary structures that limit refugees’ inclusion as equals. Yet, building social contacts with locals is essential for inclusion. This article shows the simultaneous presence of inclusion and exclusion by engaging with narratives from Syrian refugees participating in a six‐month housing project initiated in an Amsterdam neighborhood. Residents and volunteers shared responsibilities for organizing daily life in the project. The result was an unexpected combination of Granovetter’s weak and strong ties, what we call “hybrid ties,” that were embedded within neighborhood dynamics and networks. Despite occasional clashes in expectations, this community‐based housing project enabled specific forms of personal relationships (through hybrid ties) that were essential in refugee participants’ later inclusion in the Netherlands.